2000
DOI: 10.1037/0012-1649.36.3.315
|View full text |Cite
|
Sign up to set email alerts
|

How Latino American and European American adolescents discuss conflicts, sexuality, and AIDS with their mothers.

Abstract: The authors examined how the structure of mother-adolescent conversations differs by ethnic group, age, and dyadic and individual factors. Mother-adolescent dyads of European or Latino descent participated in conversations and reported on their relationship and AIDS knowledge. Latina American mothers dominated conversations more than European American mothers, independent of socioeconomic status. Mothers dominated conversations about sexuality and AIDS more than conversations about conflicts. Mothers of older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 41 publications
3
59
0
Order By: Relevance
“…25 Both mothers and daughters emphasize the importance of discussing sexuality and reproductive health, 24,26,27 yet both report that it is challenging and most often inadequate. 28,29 Little is known about the role of the family in facilitating gynecologic care for adolescents. In one qualitative study of urban minority families, girls emphasized the important role that mothers play in seeking health care before sexual debut, but they reported diffi culty transitioning from trusted familial sources of advice and care (especially mothers) to other appropriate sources of care after onset of sexual activity.…”
Section: Diane Mckee MD Ms 1 Confident Ia L C a R E F Or A D Ol mentioning
confidence: 99%
“…25 Both mothers and daughters emphasize the importance of discussing sexuality and reproductive health, 24,26,27 yet both report that it is challenging and most often inadequate. 28,29 Little is known about the role of the family in facilitating gynecologic care for adolescents. In one qualitative study of urban minority families, girls emphasized the important role that mothers play in seeking health care before sexual debut, but they reported diffi culty transitioning from trusted familial sources of advice and care (especially mothers) to other appropriate sources of care after onset of sexual activity.…”
Section: Diane Mckee MD Ms 1 Confident Ia L C a R E F Or A D Ol mentioning
confidence: 99%
“…sexuality) with their children (Gabb, 2004;Jordan, Price & Fitzgerald, 2000;Kakavoulis, 2001), especially fathers (Goldman and Bradley, 2004;Kirkman, Rosenthal & Feldman, 2003;Lefkowitz, Roma, Corona, Au & Sigman, 2000a;Lehr, Demi, Dilorio, & Facteau, 2005;Miller, Dilorio & Dudley, 2002). It has been suggested that parents feel unable to discuss these topics, such as sexuality, as they fear that they are not equipped with both the necessary skills and the knowledge to educate their children (WernerWilson & Fitzharris, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The other group of researchers that has considered emotional expression within the adolescent-parent relationship is Lefkowitz, Sigman, and colleagues (Kahlbaugh, Emotional Expression 82 Lefkowitz, Valdez, & Sigman, 1997;Lefkowitz, Kahlbaugh, Au, & Sigman, 1998;Lefkowitz, Kahlbaugh, & Sigman, 1996;Lefkowitz, Romo, Corona, Au, & Sigman, 2000). Across all studies, these researchers found that mothers displayed more affiliative behaviors than did the adolescents, whereas the adolescents showed more expressions of embarrassment and contempt than did their mothers.…”
Section: Support For Hypotheses About Differences In Emotional Expresmentioning
confidence: 94%
“…Lefkowitz, Sigman and colleagues (Kablbaugb, Lefkowitz, Valdez, & Sigman, 1997;Lefkowitz, Kablbaugb, Au, & Sigman, 1998;Lefkowitz, Kablbaugb, & Sigman, 1996;Lefkowitz, Romo, Corona, Au, & Sigman, 2000) measured the expression of specific emotions in conversations between mothers and adolescents (ages 10-15). Dyads discussed several topics that included personal conflict issues and issues about dating and sexuality.…”
Section: Emotional Expression 10mentioning
confidence: 99%
See 1 more Smart Citation